Real-World Data for Lenvatinib in Radioiodine-Refractory Differentiated Thyroid Cancer (RELEVANT): A Retrospective Multicentric Analysis of Clinical Practice in Austria. (29th November 2020) - Rendl, G.; Sipos, B.; Becherer, A.; Sorko, S.; Trummer, C.; Raderer, M.; Hitzl, W.; Ardelt, M.; Gallowitsch, H. J.; Pirich, C.
Abstract : Background . Lenvatinib has proven efficacy in progressive, radioiodine- (RAI-) refractory thyroid cancer (TC). Dose reductions are commonly performed due to decreased tolerability and adverse effects. This retrospective multicenter study analyzed overall survival (OS) and progression-free survival (PFS) and tolerability in the Austrian patient population treated with lenvatinib. Methods . Clinical data of 43 patients (25 males and 18 females) with a median age of 70 years (range: 39–91 years) and RAI-refractory TC with metastases to the lymph nodes (74%), lungs (86%), bone (35%), liver (16%), and brain (12%) were analyzed. The mean duration of treatment with lenvatinib was 26.6 ± 15.4 months with dosage reductions required in 39 patients (91%). Results . PFS after 24 months was 71% (95% CI: 56–87), and overall survival (OS) was 74% (95% CI: 60–88), respectively. OS was significantly shorter (p = 0.048 ) in patients with a daily maintenance dosage ≤ 10 mg (63%) (95% CI: 39–86) as compared to patients on ≥ 14 mg lenvatinib (82%) (95% CI: 66–98) daily. Dose reduction was noted in 39 patients (91%). Grade ≥3 toxicities (hypertension, diarrhea, weight loss, and palmar-plantar erythrodysesthesia syndrome) were most common leading to discontinuation of lenvatinib in 7 patients (16%). Conclusion . Lenvatinib showed sustained clinical efficacy in patients with metastatic RAI-refractory TC even with reduced maintenance dosages over years. The effects were comparable to the registration trial, although patients had a higher median age and, more commonly, dose reductions.